Efficacy and safety of levosimendan in patients with sepsis: a systematic review and network meta-analysis - Tan, Ruimin; Guo, He; Yang, Zinan; Yang, Huihui; Li, Qinghao; Zhu, Qiong; Du, Quansheng (Frontiers in Pharmacology, 2024)
Objective: We conducted a systematic review to assess the advantages and disadvantages of levosimendan in patients with sepsis compared with placebo, milrinone, and dobutamine and to explore the clinical efficacy of different concentrations of levosimendan.Methods: PubMed, Web of Science, Cochrane Library, Embase, CNKI, Wanfang data, VIP, and CBM databases were searched using such keywords as simendan, levosimendan, and sepsis. The search time was from the establishment of the database to July 2023. Two researchers were responsible for literature screening and data collection respectively. After the risk of bias in the included studies was evaluated, network meta-analysis was performed using R software gemtc and rjags package.Results: Thirty-two randomized controlled trials (RCTs) were included in the network meta-analysis. Meta-analysis results showed that while levosimendan significantly improved CI levels at either 0.1 ug/kg/min (mean difference [MD] [95%CrI] =0.41 [-0.43,1.4]) or 0.2 ug/kg/min (MD [95%CrI] =0.54[0.12,0.99]). Levosimendan, at either 0.075ug/kg/min (MD [95% CrI] =0.033 [-0.75,0.82]) or 0.2ug/kg/min (MD [95% CrI] =-0.014 [-0.26,0.23]), had no significant advantage in improving Lac levels. Levosimendan, at either 0.1ug/kg/min (RR [95% CrI] =0.99 [0.73,1.3]) or 0.2ug/kg/min (RR [95% CrI] =1.0 [0.88,1.2]), did not have a significant advantage in reducing mortality.The existing evidence suggests that levosimendan can significantly improve CI and lactate levels in patients with sepsis, and levosimendan at 0.1 ug/kg/min might be the optimal dose. Unfortunately, all interventions in this study failed to reduce the 28-day mortality.